PENINGKATAN PENDAPATAN PETERNAK MELALUI MANAJEMEN FEEDING PRACTICE DI KELOMPOK TERNAK ITIK USAHA BERSAMA DI DESA SIKABU-KABU KABUPATEN 50 KOTA - Sabrina Sabrina; Husmaini Husmaini; Kusnadidi Subekti; Firda Arlina (Jurnal Hilirisasi IPTEKS, 2024)
This activity aims to provide training and technology packages for improving the maintenance system, knowledge of feed ingredients, technology for producing duck feed based on local feed, restricted feeding. The ultimate goal of this activity is to increase egg production, productivity, feed cost efficiency in the context of developing and increasing farmers' income while forming / developing economically independent partner groups. This activity was carried out in Tanjung Haro Selatan, Luak District, 50 Kota Regency, West Sumatra. The partner involved in this activity is the "Duck Farmer Group "Usaha Baru" which reared egg and meat ducks. The methods used in this service program are counseling, demonstration, training, coaching and provision of technology packages, as well as observation and evaluation and data collection to measure the success parameters of the program being carried out. Based on the implementation of the community service, farmers were very enthusiastic in participating in this activity, almost 80% percent of farmers understand feeding management according to the needs of duck feed based on age level both in quality and quantity. the quality of the rations prepared by the farmer is not sufficient for the nutritional needs of ducks. Increasing egg production can be done by preparing duck rations by increasing animal protein and mineral levels in the ration. Increasing the income of duck farmers can be done by reducing production costs with rations prepared by farmers themselves sourced from local feed ingredients at a price of Rp. 6000, -.